Pick-up of fluoroquinolones from the aqueous phase via magnetically propeled microrobots: kinetics, thermodynamics, and site energy distribution analysis - Tang, Yongzheng; Jia, Wenpeng; Bao, Mutai; Qiu, Shengyao; Pi, YongRui; Liu, Chongfeng; Zhao, Jinchen (Frontiers in Marine Science, 2023)
Removing fluoroquinolones (FQs) in the marine culture tail water is crucial for the coastal marine environment. The application of a bacteria-based microrobot for FQs removal was discussed. Norfloxacin (NOR) and Levofloxacin (LEV) had static maximum adsorption capacities of 114.8 mg/g and 49.4 mg/g on magnetic microrobot, respectively. The experimental results of NOR adsorption by magnetic microrobot were well supported by the Langmuir isotherm and Elovich kinetic models. Both the Langmuir isotherm model and the pseudo-second-order kinetic model may be able to accurately represent the LEV adsorption process. The mass transfer mechanism of the NOR and LEV adsorption was divided into two steps and described better using the IPD model. The exothermic and spontaneity of the sorption process were demonstrated through the study of thermodynamics. The magnetic microrobot's heterogeneous surface was validated by the examination of site energy distribution. Additionally, it demonstrated that the majority of the NOR and LEV sorption took place at sites with energies over 4.25 kJ/mol and 17.36 kJ/mol, supporting the notion that NOR and LEV adsorption constituted a physical-chemical process. Based on the above results, the magnetic microrobot, as a new-style green bio-adsorbent, can be used to remove NOR and LEV from the mariculture tailwater potentially, economically, and effectively.